O-017 Towards self-steering microcatheters for neurointervention. (23rd July 2022) - Abah, C; Lawson, J; Simaan, N; Chitale, R
Abstract : Introduction: Neuroendovascular procedures are associated with a high level of technical complexity. Complex, tortuous, and branched vasculature must be navigated to distal intracranial sites in order to treat high-risk vascular pathologies. Neuroendovascular robotics is an emerging field with potential to improve the safety and success of these procedures. We propose a dexterous and actively steerable microcatheter for robotic-assisted neuroendovascular navigation. We present initial experimental validation of the feasibility of branch selection and active compliance of this catheter. Such technology has the potential to 1) increase technical precision, 2) reduce procedural time, 3) reduce radiation exposure, and 4) enable semi-automation of catheter navigation. Materials and Methods: We developed a multi-articulated self-steering microcatheter for neuroendovascular surgery. To enable traversal of tortuous cerebral vasculature, this catheter actively bends in two separate planes ( figure 1a ). Our system also includes series-elastic actuation for increased safety and to enable active compliance (self steering). In addition we used preoperative CT scans of the CCA and ICA to create a nominal path plan and to optimize the catheter design parameters to minimize the catheter's passive bending. A simulation study was performed to compare ad-hoc catheter design to an optimized catheter design. We also developed catheter tip tracking in bi-plane fluoroscopic images. Results: With the initial catheter prototype, branch selection was performed on mock vasculature ( figure 1b ). Using the proposed vasculature-specific catheter design optimization, we fabricated an optimal catheter for a particular anatomy, reducing the path plan error by 44% in position and 38% in orientation, and resulting in a maximal passive deflection of the catheter tip of 2.34 mm. This design was autonomously navigated in a mock CCA bifurcation phantom. The segmentation algorithm tracked a guidewire during carotid insertion with an update frequency of 10 Hz and average error 0.55 mm. Finally, we demonstrated the feasibility of active compliance of this robot. During the experiment, the catheter tip autonomously responded to forces causing it to actively steer into a channel with an unknown geometry. Conclusion: A multi-articulating catheter for neuroendovascular navigation and with active compliance for self-steering was developed along with algorithms for vasculature-specific design optimization. The catheter traversed a mock carotid bifurcation and demonstrated branch selection and active compliance. This is a first step towards semi-autonomous navigation for neuroendovascular procedures. Disclosures: C. Abah: None. J. Lawson: None. N. Simaan: None. R. Chitale: 1; C; Medtronic, Cerenovus. 2; C; Medtronic.